Cyclical construction and destruction of flood dominated floodplains in semiarid central Australia - BOURKE, MARY (My University, 1994)
The morphostratigraphy of flood plains along unconfined reaches of the Todd River, central Australia, indicate that flood plain formation is dominated by high magnitude floods. Processes of flood plain destruction include channel widening, vertical stripping, flood channel, back channel and macroturbulent scour. Flood plain construction occurs predominantly during high magnitude floods. Overbank aggradational sequences comprise a complex assemblage of depositional units which include channel and flood plain insets, terrace veneer sedimentation and channel fills separated from each other by erosional unconformities. The resultant sedimentary sequences within the flood plain is best described as chaotic. Mechanisms responsible for the construction and destruction of flood plains operate at three scales. These extend from the alteration of individual sedimentary layers to the complete removal of valley bottom aggradational sequences. The highly complex morphostratigraphy of flood plains in this region negates the application of conventional paleoenvironmental reconstruction techniques.
PUBLISHED
Keywords: Fluvial; Geomorphology; Flood; Floodplain; Arid; Desert; Smart & Sustainable Planet